Genes and miRNAs as Hurdles and Promoters of Corticospinal Tract Regeneration in Spinal Cord Injury - Boido, Marina; Vercelli, Alessandro (Frontiers in Cell and Developmental Biology, 2021)
Spinal cord injury (SCI) is a devastating lesion to the spinal cord, which determines the interruption of ascending/descending axonal tracts, the loss of supraspinal control of sensory-motor functions below the injured site, and severe autonomic disfunctions, dramatically impacting on the quality of life of the patients. After the acute inflammatory phase, the progressive formation of the astrocytic glial scar characterizes the acute-chronic phase: such scar represents one of the main obstacles to the axonal regeneration that, as known, is very limited in the central nervous system (CNS). Unfortunately, a cure for SCI is still lacking: the current clinical approaches are mainly based on early vertebral column stabilization, anti-inflammatory drug administration and rehabilitation programs. However, new experimental therapeutic strategies are under investigation, one of which is to stimulate axonal regrowth and bypass the glial scar. One major issue in axonal regrowth consists in the different genetic programs, which characterize axonal development and maturation. Here we will review the main hurdles that in adulthood limit axonal regeneration after SCI, describing the key genes, transcription factors and miRNAs involved in these processes (seen their reciprocal influencing action), with particular attention to corticospinal motor neurons located in the sensory-motor cortex and subjected to axotomy in case of SCI. We will highlight the functional complexity of the neural regeneration programs. We will also discuss if specific axon growth programs, that undergo a physiological downregulation during CNS development, could be reactivated after a spinal cord trauma to sustain regrowth, representing a new potential therapeutic approach.